Physical conditioning in post covid-19 patients to improve their aerobic capacity (RIAF. International Journal of Physical Activity, 2023)
Aerobic capacity is the property of a body to perform moderate physical activity with little fatigue and little effort, it is affected during and after COVID-19 infection. The objective of this project is to improve, through physical conditioning, the aerobic capacity of patients who suffered from SARS COVID-19. Methodology: surveys were carried out where information was collected to know the number of infected people, their recovery time and the degree of severity of the disease, among other aspects. With the data obtained, a respiratory exercise guide was obtained as a proposal that aims to recover aerobic capacity. Conclusion: it was concluded that breathing exercises are a fundamental tool for the recovery of aerobic capacity in people who suffered from SARS COVID-19. Recommendations: promote physical activity by the state as an alternative for future disease prevention.
Keywords: Physical conditioning; aerobic capacity; COVID-19